2019
DOI: 10.3390/su11205651
|View full text |Cite
|
Sign up to set email alerts
|

Relative Income and Life Satisfaction among Chinese Adults

Abstract: Life satisfaction is a key component of people’s subjective well-being. This study assessed the relationship between relative income and life satisfaction among Chinese adults, using data from a cross-sectional survey. Individual-level data (N = 1369) came from the 2016 China Genuine Progress indicator Survey (CGPiS) conducted in Beijing and Chengdu, China. Ordered logistic regressions were performed to examine the relationship between relative income and life satisfaction among CGPiS adult respondents. Respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…In China, there are obvious economic policy differences from the eastern to the western regions [30]. As a result, government investment in different regions will be affected by exploitation, increasing the sense of social inequality [31] and seriously affecting the life satisfaction of residents [32,33].…”
Section: Exploitation Theorymentioning
confidence: 99%
“…In China, there are obvious economic policy differences from the eastern to the western regions [30]. As a result, government investment in different regions will be affected by exploitation, increasing the sense of social inequality [31] and seriously affecting the life satisfaction of residents [32,33].…”
Section: Exploitation Theorymentioning
confidence: 99%
“…The existing research on subjective well-being has identified, among others, the following determinants of subjective well-being (Dolan et al , 2008; Ngoo et al , 2015): personality traits (Okun and George, 1984; Diener et al , 1999; Helliwell, 2006); socio-demographic characteristics (Fernandez and Kulik, 1981; Evans and Kelley, 2004; Blanchflower and Oswald, 2008); culture and religion (Diener, 2000; Exton et al , 2015; Ngamaba and Soni, 2017), social capital (Powdthavee, 2008; Helliwell and Putnam, 2004; Helliwell and Barrington-Leigh, 2010; Helliwell and Shun, 2011); neighborhood context (Shields et al , 2007; Sorensen, 2013; Ma et al , 2017); economic factors such as income (Easterlin, 1974, 1995; McBride, 2001; Clark et al , 2005; Deaton, 2008; Tella et al , 2010; Mikucka et al , 2017; Guan et al , 2019) and employment (Clark and Oswald, 1994; Bockerman and Ilmakunnas, 2006; Booth and van Ours, 2009; Helliwell and Huang, 2014; Baslevent and Kirmanoglu, 2014). There is also a strand of literature that analyzes the role of institutional factors, government performance and public policies in subjective well-being.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nispi gelir ve mutluluk arasındaki pozitif ilişkiyi destekleyen çok sayıda çalışma mevcuttur (Caporale, Georgellis, Tsitsianis ve Yin, 2009;Oshio, Nozaki ve Kobayashi, 2011;Tibesigwa, Visser ve Hodkinson, 2016). Bir çalışmada Çin'li yetişkinlerin çoğu nispi gelir ve yaşam memnuniyeti arasında pozitif bir ilişki olduğunu bildirmişlerdir (Guan, Qiu ve An, 2019). Bununla birlikte literatürde gelirinin başkasının gelirinden daha düşük olduğunu düşünen bireylerin daha mutsuz olduklarını bildiren çalışmalar da mevcuttur (Hopkins, 2008).…”
Section: Introductionunclassified